Separation methods in the food industry: An exploration of reverse osmosis, evaporation and freeze concentration applications / Nurul Amalia Farhana Abu Bakar and Farah Hanim Ab Hamid - Abu Bakar, Nurul Amalia Farhana; Ab Hamid, Farah Hanim (Universiti Teknologi MARA Shah Alam, 2023)
Separation method is broadly used in various industries, mainly in the food industry. Some of the applications include retaining the nutrients and concentrating fruit juices, liquid foods, and milk products. Fundamentally, the concentrated liquid product is achieved by these separation methods. Technology advances daily, impacting food quality characteristics such as flavour, colour, and texture. Production and commercialisation processes are key considerations, from conventional to modern approaches. Hence, this study aims to review the various types of separation methods with their application in food industries which are evaporation, reverse osmosis, and freeze concentration that is separated into two: suspension freeze concentration and progressive freeze concentration.